Methods of Organizing Professional and Communicative Teaching of Foreign Languages in Language Universities (Eurasian Journal of Engineering and Technology, 2023)
In our article, language teaching in foreign language teacher training programs is considered professional directions based on a general concept of professional and communicative competence. Professional communicative competence plays a dominant role in the foreign language teaching process as it is the main component of the implementation of the components of all other competencies inherent in a foreign language teacher